Analisis pembelajaran matematika materi skala dan perbandingan kelas V sekolah dasar - Wijayanti, Ririn; Kurniawan, Sandra Bayu; Budhiharto, Tri (Universitas Sebelas Maret, 2022)
The purpose of this study was to determine the learning planning, learning process and evaluation of mathematics learning on scale and comparison materials. This type of research is qualitative with a case study approach. The subjects of this study were school principals, fifth grade teachers and fifth grade students. Data collection techniques in this study were through observation, interviews and documentation. Data analysis in this study used an interactive model developed by Miles and Huberman. The results of the study showed that the fifth grade teacher at SDN 01 Tuban in planning mathematics learning on the scale and comparison material, not all indicators were carried out, there was one indicator that had not been implemented by the teacher, namely the indicator for planning procedures, types, and preparing assessment tools, this resulted in lesson planning carried out by the teacher.The process of learning mathematics on scale material and comparisons for class V SDN 01 Tuban, the teacher has carried out all indicators, but there is one indicator that has not been carried out optimally, namely demonstrating special abilities in learning mathematics, the teacher does not instill mathematical concepts with manipulative activities